CORRUPTION AND EXPLOITATIVE TENDENCIES IN AMMA DARKO’S THE HOUSEMAID - SAMUEL IDOWU, ADEWUMI,; LAWRENCE OWOLABI, EGBUWALO (IJRDO - Journal of Social Science and Humanities Research, 2017)
Corruption has varied meanings as individuals perceive it. Corruption and exploitation have interrelated relationship which relates to deliberate cheating of innocent and less privileged citizens of a society. This paper therefore, takes a prosaic view at the way some people engage in the act of corruption and equally exploit the less privileged ones in the society as reflected in Amma Darko’s text −The Housemaid. The girls drafted from the villages such as Kataso, Oriadon and others that serve as housemaids by engaging in various house chores could be seen as total exploitation. The promises given at the initial stage of contractual agreement were not followed. Such girls/housemaids were left to the vulnerable hawks hovering the streets of the big cities of Ghana.